Teachers' Perceptions of the Application of Digital Gamification-Based Problem-Based Learning (PBL) to Increase Student Engagement - Isnayah, Magfirah; Iswatiningsih , Daroe (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2025)
This study aims to describe teachers' perceptions regarding the implementation of problem-based learning (PBL) through digital gamification to enhance student engagement. Specifically, it examines teachers' views on the effects and challenges of applying digital gamification-based PBL to improve student activity. The research employs a mixed-methods approach with a sequential explanatory design. Findings indicate that teachers generally hold positive perceptions of integrating PBL with digital gamification. Teachers report that gamification makes learning more engaging and fosters active participation, including questioning, discussion, and opinion expression. Additionally, teachers observe increased enthusiasm, collaboration, and student independence in problem-solving. However, the study also identifies challenges such as limited internet access and devices, varying levels of teachers' digital proficiency, and the need for professional development to design effective digital gamification-based PBL scenarios. Factors supporting successful implementation include adequate school facilities, teacher creativity, and student motivation. Overall, the study concludes that digital gamification-based PBL has the potential to enhance student activity, although its effectiveness depends significantly on technological readiness, institutional support, and teacher pedagogical competence